Micro-entrepreneurship for dummies - Mladjenovic, Paul (--For dummies., 2013)
Tired of the 9-to-5 grind and want a way to earn or to supplement your income? Easy. The media has named the growing trend toward micro-entrepreneurship ""the Rise of the Creative Class, "" ""the Gig Life, "" or ""the freelance economy."" All of those refer to the nearly 4 million workers who were self-employed this past year, and millions of others who currently supplement their income with freelance work. While the trend has been spotted before, there's one stark difference between micro-entrepreneurs today and the ""Free Agent Nation"" citizens of the late '90s: technology. Micro-